CLINICAL AND IMMUNOLOGICAL EFFECT OF PNEUMOCOCCAL CONJUGATED VACCINES IN IMMUNOCOMPROMISED PATIENTS - A.A. Tarasova; M.P. Kostinov (Union of pediatricians of Russia, 2010)
Invasive pneumococcal infection is the most frequent cause of death in patients with immunodeficiences. The antibiotics used previously for prevention purposes are not efficient enough due to the developing antibiotic resistance. Polysaccharide pneumococcal vaccines create short-lived immunity. The overview summarizes the experience of applying conjugated pneumococcal vaccines in patients with primary immunodeficiences, HIV infection, oncological and rheumatic diseases. Key words: pneumococcal infection, pneumococcal conjugated vaccines, children, immunosuppression. (Pediatric Pharmacology. - 2010; 7(5):18-23)